2008
DOI: 10.3354/ame01198
|View full text |Cite
|
Sign up to set email alerts
|

Climate warming in winter affects the coupling between phytoplankton and bacteria during the spring bloom: a mesocosm study

Abstract: An indoor mesocosm used to determine the effect of warming on microbial communities. Inset: Recycling of organic matter inside the mesocosm is mediated by the interaction of phytoplankton and bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
89
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(99 citation statements)
references
References 39 publications
(34 reference statements)
7
89
2
Order By: Relevance
“…at 5.0°C in the Arctic, and at 2.5, 5.0 and 7.0°C in the Fjord microcosm are in agreement with observations made by Lovejoy et al (2007) in the Arctic Ocean, where there are blooms of this picoflagellate during spring and summer. In the present study, BA (bacterial abundance) and BP (bacterial production) increased when chl a concentration decreased, probably due to the increase in organic matter from excretion or cell lysis of primary producers that might stimulate bacterial growth, as proposed by Hoppe et al (2008). Moreover, empirical relationships between temperature and bacterial growth in natural bacterioplankton assemblages have shown that temperature is closely related to BP (White et al 1991, Wiebe et al 1992, Shiah & Ducklow 1994.…”
Section: Phytoplankton and Bacterioplanktonmentioning
confidence: 62%
“…at 5.0°C in the Arctic, and at 2.5, 5.0 and 7.0°C in the Fjord microcosm are in agreement with observations made by Lovejoy et al (2007) in the Arctic Ocean, where there are blooms of this picoflagellate during spring and summer. In the present study, BA (bacterial abundance) and BP (bacterial production) increased when chl a concentration decreased, probably due to the increase in organic matter from excretion or cell lysis of primary producers that might stimulate bacterial growth, as proposed by Hoppe et al (2008). Moreover, empirical relationships between temperature and bacterial growth in natural bacterioplankton assemblages have shown that temperature is closely related to BP (White et al 1991, Wiebe et al 1992, Shiah & Ducklow 1994.…”
Section: Phytoplankton and Bacterioplanktonmentioning
confidence: 62%
“…Two main approaches have been followed: (1) experimental approaches designed as factorial experiments, incubating macroalgae for days or months at different growth temperatures according to the future predicted scenarios, and evaluating the interactive responses with other variables, such as acidification, UV radiation (UVR), and nutrient availability, amongst others (Baulch et al 2003, Hoppe et al 2008, Porzio et al 2011and (2) field studies of seaweeds growing at their temperature limit for growth and reproduction, while monitoring the temporal and spatial variation of temperature and other variables (Viejo et al 2011, Martínez et al 2012. Most investigations have been conducted on individual species separately, rather than communities (Olabarria et al 2013), although it has been reported that community-level impacts might be less noticeable (Kroeker et al 2010).…”
Section: )mentioning
confidence: 99%
“…PPr can also show a positive response to temperature, although this has not been as well documented as for bacteria (Vrede et al 1999). The response to temperature may, thus, be greater for BP than PPr; therefore, increasing temperatures may increase the BP : PPr ratio (Mü ren et al 2005;Hoppe et al 2008). Physical attributes of lake ecosystems such as mean depth and lake area may also affect PPr and BP, i.e., large, shallow lakes tend to have higher sediment resuspension and P release from sediments than deep lakes (Kalff 2003).…”
mentioning
confidence: 99%